BIBLIOMETRIC ANALYSIS ON FORAGE CACTUS PRODUCTION, MANAGEMENT AND USE IN ANIMAL NUTRITION: DEVELOPMENT, CURRENT STATUS AND FUTURE RESEARCH - Herrera-Angulo, Ana M.; Ferreira dos Santos, Mércia Virginia; da Cunha, Márcio Vieira; Leão de Mello, Alexandre Carneiro; Caraciolo Ferreira, Rinaldo Luiz; Diniz, Williane Patrícia; Mora-Luna, Robert E. (Chilean Journal of Agricultural & Animal Sciences, 2023)
Forage cactus (FC) is a perennial crop primarily developed in semi-arid regions. In Brazil, it is one of the main feed sources for ruminants during the dry season. However, scientific research and publication on FC seem limited and recent. Bibliometric studies allow measuring publication patterns and understanding the evolution of scientific production. Thus, a bibliometric analysis was carried out to evaluate the scientific production on productive aspects, management, and use of FC in animal feed (1800-June 2022). The literature search was based on keywords, including “cactus, cacti, nopal, prickly pear, palma forrageira, cacto, Nopalea, Opuntia, forage, forragem, and forraje”. Data were analyzed using the Bibliometrix tool based on the R language through the Biblioshiny interface. A total of 514 publications were identified, with a predominance of research articles (92.6%). Scientific production includes authors from 40 countries, highlighting Brazil (1094 authors). The main sources were: Revista Brasileira de Zootecnia, Acta Horticulturae, Tropical Animal Health and Production, Revista Caatinga, Journal of the Professional Association for Cactus Development, and Revista Brasileira de Engenharia Agrícola e Ambiental. The 10 most frequent words were: Opuntia, Semiarid, Nopalea, Forage, Cactaceae, Opuntia fícus-indica, Cactus, Cactus pear, Intake, and Digestibility. Scientific production on FC is led by researchers from Brazil, notably from Northeastern Brazil. Publications on the economic evaluation, establishment and maintenance of promising species, soil conservation, micronutrient content and the use of FC as a supplementary source of water, are less frequent. These sub-areas suggest future lines of research that may be inter-institutional to increase collaboration networks between countries.